Imaginaires zoolinguistiques : des langues animales dans la fiction littéraire - Sophie Milcent-Lawson (Itinéraires)
It is surprising that among the imaginary languages invented in fictional literature animal languages have not yet been subjected to a systematic linguistic investigation. And yet, from Aristophanes in antiquity through the Utopian literature of the seventeenth and eighteenth centuries to ultra-contemporary fiction, numerous authors have not been content to simply give a (human) voice to animals and have attempted instead to forge uglossias differing from human languages. These linguistic productions attributed to different species (frogs, birds, horses, lions, bulls, donkeys, seals, hens, dogs, monkeys…) are characterized by other phonological traits, other morphological systems, other grammars. This article aims to conduct an inquiry into linguistic imaginaries by focusing on the representations of imaginary animal languages as they are evidenced in the fictional literature of different periods, from satire through science-fiction to ludic fantasy. Grounded in the analysis of a sample of “animal” utterances drawn from fictional literature, it will attempt to identify the characteristics of this imaginary zoolinguistics.